Analisis Tingkat Penerimaan Mahasiswa Terhadap SIAM Poltekkes Kemenkes Riau Menggunakan TAM dan Webqual - Muhammad Irzan; Syaifullah Syaifullah; Muhammad Luthf Hamzah; Mediyantiwi Rahmawita (JURIKOM (Jurnal Riset Komputer), 2022)
The Riau Ministry of Health Poltekkes is a vocational tertiary institution in the Riau province health sector that has implemented a Student Academic Information System (SIAM) that supports management in the academic section, as well as a means of information and communication. But in its implementation there are still some problems, for example errors in several menus in SIAM, there is no interaction between admin staff and students as SIAM users, features that are not yet optimal in SIAM, and information on SIAM is not updated. This study aims to determine the level of student acceptance of SIAM Poltekkes Riau Ministry of Health using the Technology Acceptance Model (TAM) and Webqual methods and provide recommendations for problems that arise. Respondents in this study were 93 active students and used SEM-PLS for data processing. From the output of the analysis, it can be stated that the level of student acceptance of SIAM is good, which has a value of 13.374. This is because SIAM is easy to use, makes it easier for students to find academic information, the information is quite detailed and easy to understand, and students feel that using SIAM is the right and wise idea so that students have an interest in using SIAM. The recommendations proposed are, fixing errors in the source code so as to make SIAM easy to access and use for students. intention and interest in student behavior to use SIAM and provide encouragement so that students always use SIAM